Loss of supernumerary axons during neuronal morphogenesis - Heathcote, RD (J Neurosci, 1985)
The morphogenesis of individual neurons was investigated in the cardiac ganglion of the frog. Intracellular injection of horseradish peroxidase shows that mature neurons lack dendrites and have a single axon. Early in development, more than half of the neurons are multipolar and have as many as four processes emanating from their cell body. The most likely mechanism for the developmental transformation of larval neurons is that the supernumerary processes are pruned from the cell body. Supernumerary processes in larval neurons have features characteristic of axons. The processes of larval neurons can be highly branched and extend throughout the target with distinctive varicosities along the length of each process. Electron microscopy shows that all processes of individually injected cells contain clusters of vesicles apposed to active zones. Thus, the larval cardiac ganglion neuron is capable of extending more than one axon from its cell body.